Loudspeaker faults detection using artificial intelligence - Mohamad Radzi Saad (School of Mechatronic Engineering, 2013)
The purpose of this research is to develop the loudspeaker fault detection model using AI which will be applied in the production line for revealing faulty loudspeaker.